The Origins of the Furnace Motif From Magico-Religious Ritual to Early Modern Tale of Makeability - Wauters, Wendy (2020)
The article delves into the fiery furnace motif and its evocations of the healing and makeability of men. Building on previous research conducted in religious history, art history and anthropology, a diachronic analysis of the textual and visual traditions of this motif is made. At its base lies the idea that the natural phenomenon of fire has a transformative power. This belief is present in several magico-religious rituals and in the visual imprint within Christian iconographical tradition. Both manifestations exist in conjunction and their evolution is intertwined. Herein lie the roots of the early modern secular motif of the furnace as a place of metaphorical transformation. Society may not have been aware of these previous attitudes, but the urban context does provide a fertile breeding ground for motifs such as The Rejuvenation Furnace and the so-called Baker of Eeklo . From the point of view of Christian ethics, it is interesting that the concentration of the furnace motif can serve as a seismograph of fluctuations in morality.
Keywords: furnace motif; Iconography; magico-religious ritual; makeability of men; Transformation